INTERNALISASI NILAI PROFIL PELAJAR RAHMATAN LIL’ALAMIN MELALUI KEGIATAN PLKJ DI MA PERSIS 297 CINGAMBUL KAB. MAJALENGKA - Ade Yuliyanti (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
The independent curriculum gives freedom and authority to madrasas to develop madrasah operational curricula in accordance with the potential and resources in managing education to improve the quality and competitiveness of madrasas to create independent and high-achieving madrasas. Apart from that, it also provides freedom in forming character, fostering critical, creative and courage. innovative for students which is colored by religious values, namely the value of rahmatan lil a'alamin. freedom of management and character formation. MA PERSIS 297 has a program that is typical of Madrasah Aliyah PERSIS, namely the Khidmah Jamiyyah Training Program (PLKJ). This program is an integrated program between academic abilities and social skills which aims to gain real experience in serving in the community in a directed and measurable way. apply the knowledge gained during education. The approach in this research uses a qualitative descriptive approach with a field research type of research with data analysis using the Miles and Huberman model. The agenda of the PLKJ research results is teaching practice, Majlis taklim, Friday sermons, Tabligh akbar, Rihlah Motivation, social service, activities according to local needs, there is an internalization of the values ​​of Rahmatan Lil Alamin's student profile which is integrated into the Pancasila student profile. Strengthening the Pancasila student profile and the Rahmatan Lil Alamin student profile is an optimal means of encouraging students to become lifelong learners who are competent, have character and behave in accordance with the values ​​of Pancasila, and Rahmatan Lil Alamin Islam.